Strategi Guru PAI dalam Menanamkan Nilai-nilai Moderasi Beragama di SMA Negeri 2 Bukittinggi - Putra, Romi; Charles, Charles (TSAQOFAH, 2023)
The PAI teacher's strategy in implementing tolerance values is obtained by developing a moderate attitude towards religion in students. It means nothing other than this personal piety, it can be seen that being a teacher of Islamic religious education is taught in class, he gives the right for non-Muslim students to attend lessons or not to study religions other than their own, the beliefs provided are in accordance with the beliefs they embrace. The key informants or people who act as information providers in this research are PAI teachers and the supporting informants are students. The author collects data using observation, interview and documentation techniques. Then the data that the researchers obtained were processed using descriptive data analysis techniques and data triangulation, namely by comparing data obtained from observations, interviews and documentation. Based on the results of this study, it can be concluded that the PAI teacher's strategy in instilling values Religious moderation is inseparable from the teacher's implementation of an upright attitude, a middle attitude, an attitude of tolerance, anti-violence and changes in thinking for students to understand religious moderation. Researchers are very interested in doing this research because teachers use the implementation of religious moderation with thinking strategies for students.